Common Neurosurgical Conditions in the Pediatric Practice : Recognition and Management - Greenfield, Jeffrey P.; Long, Caroline B. (Springer New York : Imprint: Springer, 2017)
This unique title is designed to illustrate and foster how a closer working relationship between pediatricians and subspecialists can make childhood medicine work more seamlessly. Despite the common lack of training for pediatricians in pediatric neurosurgery, they are challenged almost daily with caring for children with neurologic conditions. Common Neurological Conditions in the Pediatric Practice is replete with a wide range of instructional case vignettes and is organized into sections that loosely approximate the neurologic development of a child and address issues that are commonly encountered. The first section reviews neurologic development and birth related trauma commonly seen in the neonatal intensive care unit. The second part addresses findings commonly encountered by a pediatrician in a child's first month of life. The third section is a comprehensive review of hydrocephalus. Part four describes state of the art imaging techniques for the central nervous system in children, from pre-natal ultrasound through MRI and CT; and the fifth part consists of individual explorations of common neurosurgical conditions that many pediatricians are uncomfortable managing, including brain tumors, spasticity, and vascular lesions to use as a reference tool when caring for a complex neurosurgical patient. Finally a series of chapters related to head trauma, including sections on non-accidental trauma and concussion management, completes the text.- Resumé vydavatel
Keywords: dětská neurochirurgie; neonatologie; novorozenci; nemoci nervového systému; pediatric neurosurgery; neonatology; newborns; nervous system diseases; elektronické knihy; sborníky; electronic books; papers of several authors